Overview of Effect of Plastic Waste Pollution on Marine Environment - Agha, Hasan Mohammed Hamid; Saleh, Ali Mohammed; Mahdi, Hadi Hamdi; Mohammed, Amjad Abdulhadi; Allaq, Abdulmutalib Alabeed Alkamil (Journal of Asian Scientific Research, 2022)
Environmental pollution is one of the most important and critical problems facing the planet and threatening the ecosystem in all its forms. Due to the large quantities of plastic manufactured in different parts of the world and the difficulty of decomposing plastic products, which have a decomposition period of decades. As well as considering the marine environment as one of the most vulnerable ecosystems to pollution with plastic waste, and at the same time, people do not pay attention to this disaster, which directly affects the rest of the environmental systems and causes serious changes to the ecosystem. In this paper, we tried to review some of the direct effects of plastic waste on marine organisms such as coral reefs and sea turtles. As well as review the impact of these organisms’ damage on the ecosystem in general. This paper recommends some solutions that will reduce the huge quantities of plastic waste and how to treat it and try to legalize production to control the amount of plastic waste previously produced during the past decades.